2007
DOI: 10.1371/journal.pone.0000310
|View full text |Cite
|
Sign up to set email alerts
|

Genes Involved in the Balance between Neuronal Survival and Death during Inflammation

Abstract: Glucocorticoids are potent regulators of the innate immune response, and alteration in this inhibitory feedback has detrimental consequences for the neural tissue. This study profiled and investigated functionally candidate genes mediating this switch between cell survival and death during an acute inflammatory reaction subsequent to the absence of glucocorticoid signaling. Oligonucleotide microarray analysis revealed that following lipopolysaccharide (LPS) intracerebral administration at striatum level, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…In respect to the association between Cp and Tf, a previous review article suggested that the transfer of iron was regulated by both CP and Tf and that activity of Cp was modulated by Tf [47]. Cp plays a important role in iron metabolism [48]. These strands support the present finding that everolimus might act mTOR signaling by increasing serum levels of Cp and Tf.…”
Section: Discussionsupporting
confidence: 84%
“…In respect to the association between Cp and Tf, a previous review article suggested that the transfer of iron was regulated by both CP and Tf and that activity of Cp was modulated by Tf [47]. Cp plays a important role in iron metabolism [48]. These strands support the present finding that everolimus might act mTOR signaling by increasing serum levels of Cp and Tf.…”
Section: Discussionsupporting
confidence: 84%
“…As detailed above, CD36 seems to be multifunctional in terms of signaling, phagocytosis, and lipid metabolism, and its induction by intracerebrally delivered LPS in the CNS is greatly restricted (Rivest et al, unpublished data). According to our previous microarray study (Glezer et al, 2007), Cd44 is among the genes highly induced upon LPS stimulation, whereas Cd83-associated transcript is limited to a small myeloid population in conditions under which antiinflammatory feedback is absent. CD44 function is most related to adhesion, and it has been correlated with ␥-secretase signaling, which is relevant to Alzheimer's disease pathology (Koo and Kopan, 2004).…”
Section: Immune Surface Molecules and Brain Circuitrymentioning
confidence: 96%
“…Indeed, Cd83 mRNA has long been known to be expressed in brain tissue according to Northern blot experiments (Twist et al, 1998), but the cellular site of expression was never explored. We previously reported that Cd44 and Cd83 transcripts are induced in brain Iba-1-positive myeloid cells by LPS in an endogenous glucocorticoid (GC)-dependent manner and in the absence of GCs signaling, respectively (Glezer et al, 2007). In addition, CD44 protein expression was carefully studied earlier in the context of nerve transection and brain trauma (Jones et al, 2000).…”
Section: Immune Surface Molecules and Brain Circuitrymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have suggested that Lcn2 may play a similar role in sensitizing microglia and astrocytes in vitro to cell death induced by cytotoxic agents such as nitric oxide (Lee et al, 2007(Lee et al, , 2009). In the CNS, expression of Lcn2 has been reported in the choroid plexus in response to peripheral lipopolysaccharide (LPS) administration (Marques et al, 2008), as well as in the striatum after intrastriatal injections of LPS (Glezer et al, 2007). Its expression was also reported to be upregulated in a microarray analysis of SCI tissue (De Biase et al, 2005).…”
Section: Introductionmentioning
confidence: 99%